Application of DNA barcoding for the identification of plant species of industrial relevance (INNOTEC, 2020)
The market for botanical products is growing worldwide due to consumers preference for natural products. This makes them targets for adulteration, which is more common and difficult to detect in industrialized derivatives. It is critical to have reliable procedures that allow their authentication. In this study, DNA-based molecular tools were applied to generate applied genomic information to classify samples of fresh and industrialized aromatic and medicinal herbs. The work was based on the DNA Barcoding strategy using fresh tissue samples of known taxonomic identity (references) and industrialized samples. The results obtained indicate that the rbcL and matK markers are amplifiable with the primers used, obtaining high quality bi-directional sequences in the case of fresh tissue in 83% of the cases for rbcL and in 63% of the cases for matK. In the industrialized samples the values were 50 and 35% respectively. The BOLD tool allowed the classification of most of the samples. This methodology is a useful and accessible tool that allows the classification in groups, although its performance is limited by the representation of the species in the databases.
Keywords: DNA; Aromatic herbs; Medicinal herbs; Classification